Convective heat transfer in porous media - Mahmoudi, Yasser; Hooman, Kamel; Vafai, K. (CRC Press, 2020)
"Focussing on heat transfer in porous media, this book covers recent advances in micro/macro scales. Apart from introducing heat flux bifurcation and splitting within porous media, it highlights two-phase flow, nanofluids, wicking and convection in bi-disperse porous media. New methods in modelling heat and transport in porous media such as pore-scale analysis and Lattice-Boltzmann methods are introduced. The book covers related engineering applications such as enhanced geothermal systems, biological tissues, porous burners, solar systems, transpiration cooling in aerospace, heat transfer enhancement and electronic cooling, drying and soil evaporation, foam heat exchangers and energy storage"-- Provided by publisher
Keywords: Porous materials -- Thermal properties.; Heat -- Transmission.; Heat -- Convection.; elektronické knihy; electronic books